Nodulation by Sinorhizobium meliloti originated from a mining soil alleviates Cd toxicity and increases Cd-phytoextraction in Medicago sativa L. - Ghnaya, Tahar; Mnassri, Majda; Ghabriche, Rim; Wali, Mariem; Poschenrieder, Charlotte; Lutts, Stanley; Abdelly, Chedly (Frontiers in Plant Science, 2015)
Besides their role in nitrogen supply to the host plants as a result of symbiotic N fixation, the association between legumes and Rhizobium could be useful for the rehabilitation of metal-contaminated soils by phytoextraction. A major limitation presents the metal-sensitivity of the bacterial strains. The aim of this work was to explore the usefulness of Sinorhizobium meliloti originated from a mining site for Cd phytoextraction by Medicago sativa. Inoculated and non-inoculated plants were cultivated for 60 d on soils containing 50 and/or 100 mg Cd kg−1 soil. The inoculation hindered the occurrence of Cd- induced toxicity symptoms that appeared in the shoots of non-inoculated plants. This positive effect of S. meliloti colonization was accompanied by an increase in biomass production and improved nutrient acquisition comparatively to non-inoculated plants. Nodulation enhanced Cd absorption by the roots and Cd translocation to the shoots. The increase of plant biomass concomitantly with the increase of Cd shoot concentration in inoculated plants led to higher potential of Cd-phytoextraction in these plants. In the presence of 50 mg Cd kg−1 in the soil, the amounts of Cd extracted in the shoots were 58 and 178 μg plant−1 in non-inoculated and inoculated plants, respectively. This study demonstrates that this association M. sativa-S. meliloti may be an efficient biological system to extract Cd from contaminated soils.